Multiple maxillary periodontal abscesses as a manifestation of post-coronavirus disease 2019 mucormycosis: a case report - Hossein Khoshkhou; Mahboube Hasheminasab; Daryoush Goudarzi Pour; Raika Jamali; Ghazal Morshedzadeh Tehrani; Neda Moslemi (Journal of Medical Case Reports, 2023)
Abstract Background Coronavirus disease 2019 makes patients more susceptible to superinfection of fungal disease as a consequence of immunological system impairment. Mucormycosis is a fungal infection that is rare but has a high mortality rate and mostly affects patients with poorly controlled diabetes mellitus or those receiving corticosteroids. Case presentation Here, we present a case of post-coronavirus disease 2019 mucormycosis in a 37-year-old Persian male presenting with multiple periodontal abscess with purulent discharge and necrosis of maxillary bone (without oroantral communication). Surgical debridement following antifungal therapy was the treatment of choice. Conclusion Early diagnosis and immediate referral are the cornerstone of comprehensive treatment.